2007
DOI: 10.1002/jnr.21442
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic membrane properties and morphological characteristics of interneurons in the rat supratrigeminal region

Abstract: The membrane properties and morphological features of interneurons in the supratrigeminal area (SupV) were studied in rat brain slices using whole-cell patch clamp recording techniques. We classified three morphological types of neurons as fusiform, pyramidal, and multipolar and four physiological types of neurons according to their discharge pattern in response to a 1-sec depolarizing current pulse from -80 mV. Single-spike neurons responded with a single spike, phasic neurons showed an initial burst of spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 59 publications
(100 reference statements)
5
25
0
Order By: Relevance
“…Intracellular staining of four SupV premotor neurons also shows that there were at least three patterns of axonal projection to the MoV. Recently, Hsiao et al (2007) reported a morphological and electrophysiological diversity in SupV neurons, although the SupV neurons recorded in their study were not identified as premotor neurons for targeting the MoV. Such diversities of SupV premotor neurons may indicate that those neurons play a wide variety of roles in orofacial motor function.…”
Section: Roles Of Premotor Neurons In the Supvmentioning
confidence: 86%
See 1 more Smart Citation
“…Intracellular staining of four SupV premotor neurons also shows that there were at least three patterns of axonal projection to the MoV. Recently, Hsiao et al (2007) reported a morphological and electrophysiological diversity in SupV neurons, although the SupV neurons recorded in their study were not identified as premotor neurons for targeting the MoV. Such diversities of SupV premotor neurons may indicate that those neurons play a wide variety of roles in orofacial motor function.…”
Section: Roles Of Premotor Neurons In the Supvmentioning
confidence: 86%
“…In anesthetized adult rats, the rhythmic neuronal activity corresponding to the masticatory rhythm during cortically induced fictive mastication can be recorded from the SupV (Inoue et al 1992). Furthermore, Hsiao et al (2007) showed that some of these neurons have intrinsic burst-generating capabilities. Thus it is possible that SupV neurons are involved in generation of suckling and/or masticatory rhythm.…”
Section: Roles Of Premotor Neurons In the Supvmentioning
confidence: 99%
“…It is well-known that several neurons in the CNS exhibit subthreshold oscillations and such oscillations play a role in controlling spike timing and network activity (Klink and Alonso, 1993;Leung and Yu, 1998;Hu et al, 2002;Hsiao et al, 2007). Although the specific mixture of ionic currents responsible for subthreshold membrane potential oscillations may vary in different neuronal populations (Klink and Alonso, 1993;Leung and Yu, 1998;Hu et al, 2002), there is evidence that key players in the generation of subthreshold oscillations are inward currents such as the persistent Na 1 current (Klink and Alonso, 1993;Hu et al, 2002;Hsiao et al, 2007), and the I h (White et al, 1995;Hu et al, 2002), as well as several K 1 outward currents such as leak currents (Klink and Alonso, 1993), the I M (Hu et al, 2002;Yoshida and Alonso, 2007) and the I A (Hsiao et al, 2007). No effect of bAP on the persistent sodium current, leak current, I h or I M has been reported so far , however, several reports have suggested that bAP may modulate I A .…”
Section: Discussionmentioning
confidence: 99%
“…A second pattern, adapting firing, especially within 500 ms, is less common (Buss et al 2003;Iwasaki et al 2008;Melnick et al 2004a), although some neurons cease firing within 200 ms (Li et al 2003(Li et al , 2004b. A third pattern, delayed-onset repetitive firing, is of similar prevalence to adapting firing; delays vary in duration between preparations and between successive stimuli (Hochman et al 1997;Hounsgaard and Midtgaard 1988;Hsiao et al 2007;McQuiston and Katz 2001;Ruscheweyh et al 2004). Finally, single firing is the least common response to current injection (Iwasaki et al 2008;Reyes et al 1994;Waddell and Lawson 1990); the majority of single-firing neurons fire additional action potentials when larger currents are injected (Erisir et al 1999;Garrido-Sanabria et al 2007; Mo et al 2002), but some remain single firing (Gamkrelidze et al 1998;Lin 1997).…”
mentioning
confidence: 94%